[View From Top of Eldfell] - Streng, Evelyn Fiedler (1975)
Photograph of the view of the ocean from the top of Eldfell. The black and red mountain sits in the bottom right corner, dusted in white and red spots. White clouds and fumes cover the top of the photograph, coming from the top of the mountain. A green island sits in the grey water in the background to the left.